1997
DOI: 10.1149/1.1837522
|View full text |Cite
|
Sign up to set email alerts
|

Highly Textured Films of Layered Metal Disulfide 2H‐  WS 2 : Preparation and Optoelectronic Properties

Abstract: Highly textured films of 2H‐ WS2 can be obtained by sulfurization of up to 4 μm thick WO3 layers in the presence of hydrogen using amorphous (quartz glass, glassy carbon) or crystalline (sapphire, muscovite, highly oriented pyrolytic graphite) substrates. Best conditions have been found employing (00.1) oriented sapphire substrates with a 5 nm thick nickel layer interposed between substrate and oxide film (0.5 to 4 μm thickness) and a reaction temperature ranging from 973 to 1173 K. Depending on time the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 1 publication
3
52
0
Order By: Relevance
“…19 and the references therein, as WS 2 is widely utilized for n/pdoped field effect transistors, for example. 20 Experimentally, synthesis and characterization of graphene on WS 2 have been reported in Ref. 4, claiming that a device based on this system can operate at room temperature with good current modulating capacity.…”
Section: 2mentioning
confidence: 96%
“…19 and the references therein, as WS 2 is widely utilized for n/pdoped field effect transistors, for example. 20 Experimentally, synthesis and characterization of graphene on WS 2 have been reported in Ref. 4, claiming that a device based on this system can operate at room temperature with good current modulating capacity.…”
Section: 2mentioning
confidence: 96%
“…[16][17][18][19] Often some kind of surfactant or crystallization promoter, such as sodium, nickel, or cobalt, was used to improve the crystallographic quality and hence the photosensitivity of these films. [19][20][21][22][23] Such promoters were investigated especially with respect to its ability to induce a pronounced ͑001͒-textured film growth, i.e., with the van der Waals planes parallel to the substrate surface. The role of nickel for the crystal growth promotion was demonstrated by Regula et al, 22 who showed that liquid NiS x droplets dissolve WS 2 and form a supersaturated solution for the liquid-phase growth of large ͑001͒-oriented WS 2 crystallites.…”
Section: Introductionmentioning
confidence: 99%
“…Inside TMDCs, the bondings are a combination of intralayer covalent-ionic bonds and the much weaker van der Waals interactions between intersandwiched layers [10]. Hence, because their structure is similar to that of graphite, TMDCs can potentially form a variety of low-dimensional structures, such as 1-D nanotubes [11,12] and 2-D graphene-like sheets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, 2-D MX 2 layers have aroused broad interest because of their many promising applications in the fields of electronics [13][14][15], optoelectronics [16], thermoelectrics [17][18][19], ferroelectrics [20], photodetectors [24], and photocatalysis [25,26]. Except for Group VB dichalcogenides [14], most TMDC single layers are semiconductors, with sizable band gaps in the range of the visible or infrared light regime, making them promising candidates for solar cells [21].…”
Section: Introductionmentioning
confidence: 99%